ANALYSIS OF COMBINED CONVECTION AND RADIATION HEAT TRANSFER IN PRESENCE OF NONGRAY CARBONDIOXIDE GAS SUBJECTED TO COLLIMATED IRRADIATION (International Journal of Engineering Sciences & Management Research, 2016)
The current study addresses the interaction phenomenon of combined natural convection with radiation in presence of radiatively active Nongray medium inside a two dimensional enclosure. The left wall is radiatively semitransparent and is subjected to collimated irradiation. All walls are assumed to be gray except, diffuse, except the semitransparent wall which is specular in nature. The variation of properties (k, ρ, μ) with temperature has been taken into consideration to make the investigation realistic. The finite volume discretization has been adopted for numerical simulation. The results are depicted through isotherm and streamline patterns. The effects of influencing parameters on Nusselt Number have also been illustrated.